2014
DOI: 10.1016/j.tins.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Control of neural circuit formation by leucine-rich repeat proteins

Abstract: The function of neural circuits depends on the precise connectivity between populations of neurons. Increasing evidence indicates that disruptions in excitatory or inhibitory synapse formation or function lead to excitation/inhibition (E/I) imbalances and contribute to neurodevelopmental and psychiatric disorders. Leucine-rich repeat (LRR)-containing surface proteins have emerged as key organizers of excitatory and inhibitory synapses. Distinct LRR proteins are expressed in different cell types and interact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 123 publications
0
59
0
Order By: Relevance
“…Our results support this hypothesis. Repeats, particularly leucine-rich repeats (LRRs) and fibronectin repeats, have also been implicated in neural development in earlier studies (Dolan et al 2007; de Wit et al 2011; de Wit and Ghosh 2014). It has been observed that LRR families involved in neural development experienced many gene duplications in higher animals compared with worms (Dolan et al 2007) and that the number of repeat units in those families is highly variable (Dolan et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Our results support this hypothesis. Repeats, particularly leucine-rich repeats (LRRs) and fibronectin repeats, have also been implicated in neural development in earlier studies (Dolan et al 2007; de Wit et al 2011; de Wit and Ghosh 2014). It has been observed that LRR families involved in neural development experienced many gene duplications in higher animals compared with worms (Dolan et al 2007) and that the number of repeat units in those families is highly variable (Dolan et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence indicates that disruption in excitatory and inhibitory synapse formation and function, leads to excitation/inhibition imbalances and contributes to both neurodegenerative and neurodevelopmental disorders [18]. However, neuronal activity and connectivity by themselves provide an incomplete understanding of the onset and progression of neurodegenerative and neurodevelopmental diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct LRR protein families are highly enriched in the CNS, especially in the hippocampus, where they play a critical role in organizing synaptic connections into functional neural circuits. Given their crucial role in the organization of neuronal connectivity, it seems likely that dysfunctions in LRR genes or in their binding partners could compromise neuronal function and lead to neurodevelopmental and neuropsychiatric disorders [18].…”
Section: Introductionmentioning
confidence: 99%